Awareness of Oral Hygiene Aids among General Population - J. Manju1, C. Krithika2 , P.R.Koteshwari 3 , G. Manoj Kumar3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: The objective of this study was to assess the knowledge of oral hygiene aids among general population. Method: The study was conducted on general population in and around Chennai. A total of 100 members were selected and self-assessed questionnaire was formulated to assess the awareness on oral hygiene aids Result: About 72% of the population are aware of the commonly available oral hygiene aids; 42% population used tooth paste and brush as a method of cleaning their teeth; 50% brushed once daily; 51% used soft brushes to brush; 54% of the population change their bushes only after 6 months; 44% followed circular motion to brush their teeth; 43% don’t use mouthwash; 49% of population media is the source of information; to about 83% of population know the importance of oral hygiene. Conclusion: The present study shows better knowledge and awareness of oral hygiene aids but the oral hygiene practice seemed to be non-satisfactory. The awareness regarding the usage of oral hygiene aids, indicates that a mass educative programme should be conducted among the general population.